Implementasi Problem Based Learning (PBL) Menggunakan Exelearning Untuk Meningkatkan Kemampuan Kognitif Dan Kemampuan Berfikir Kritis Siswa - Rohmat Rohmat; Sulistyono Sulistyono; Anna Fitri Hindriana (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
The low understanding of the students on the biology materials in the learning process of science causes the students' repetition value to be low. With by this background the aim of this research was to know the cognitive ability and critical thinking ability of students who in their learning process apply Problem Based Learning (PBL) learning model by using exelearning. The sample in this research is 40 students of class VIII in MTs Negeri 2 Cirebon. The sampling technique used in determining the sample was Purposive random sampling. This research uses experimental method with one class given treatment and other class not given treatment that acts as control. From the result of data analysis, it can be concluded that the cognitive ability and critical thinking ability of students using PBL (Problem Based Learning) model with exelearning assistance was superior compared to using the lecture model on the concept of human excretion system. The improvement of students' cognitive ability in the experimental class seen from the N-Gain value reached 0.73 (high) compared to the control class which only reached 0.13 (low). As for the increase gain N-Gain value of 0.71 (height) and control class reaches the value of 0.25 (low)Keywords: Problem Based Learning Model (PBL);  Exelearning; Cognitive Ability; Critical Thinking Skill